WHAT FACTORS CONTROL MECHANICAL EROSION RATES? - Harrison C.G.A. (My University, 2000)
Mechanical erosion rates are important factors in understanding how continents evolve. Mechanical erosion is much faster than chemical erosion, especially for highly elevated regions of the Earth's surface. It is a principal way in which mountain ranges are removed, exposing deep metamorphic roots, which comprise much of the older portions of the continental masses. In addition, there has to be a long-term balance between erosion and mountain building. A new data set allows us to explore in greater detail some of the many factors which control mechanical erosion rates. The most important factors are some expression of the average slope of a drainage basin, some measurement of the amount of water available for erosion, some environmental measurements, and also a measurement of basin length, for which we have no good explanation. The estimate of global mechanical erosion rate obtained here is considerably lower than those obtained by some other workers, some of whom have concentrated on the fact that smaller river basins tend to get eroded faster than larger basins, and it is mainly smaller basins which have not been measured and which are therefore not allowed for by simple arithmetic averaging of observed erosion rates. It is shown here that although smaller basins are eroded faster, this is mainly because they are steeper than larger basins. We also show that extrapolation of current data to smaller basins does not work because the observed continental area which is draining to the ocean cannot be attained by the simplest extrapolation scheme.
Keywords: MOUNTAIN BUILDING; HYPSOGRAPHY; MECHANICAL EROSION; RIVER DRAINAGE BASINS; PRECIPITATION; RUNOFF; SLOPE